Structural and functional diversity among Type III restriction-modification systems that confer host DNA protection via methylation of the N4 atom of cytosine. - Iain A Murray (Public Library of Science (PLoS), 2021)
We report a new subgroup of Type III Restriction-Modification systems that use m4C methylation for host protection. Recognition specificities for six such systems, each recognizing a novel motif, have been determined using single molecule real-time DNA sequencing. In contrast to all previously characterized Type III systems which modify adenine to m6A, protective methylation of the host genome in these new systems is achieved by the N4-methylation of a cytosine base in one strand of an asymmetric 4 to 6 base pair recognition motif. Type III systems are heterotrimeric enzyme complexes containing a single copy of an ATP-dependent restriction endonuclease-helicase (Res) and a dimeric DNA methyltransferase (Mod). The Type III Mods are beta-class amino-methyltransferases, examples of which form either N6-methyl adenine or N4-methyl cytosine in Type II RM systems. The Type III m4C Mod and Res proteins are diverged, suggesting ancient origin or that m4C modification has arisen from m6A MTases multiple times in diverged lineages. Two of the systems, from thermophilic organisms, required expression of both Mod and Res to efficiently methylate an E. coli host, unlike previous findings that Mod alone is proficient at modification, suggesting that the division of labor between protective methylation and restriction activities is atypical in these systems. Two of the characterized systems, and many homologous putative systems, appear to include a third protein; a conserved putative helicase/ATPase subunit of unknown function and located 5' of the mod gene. The function of this additional ATPase is not yet known, but close homologs co-localize with the typical Mod and Res genes in hundreds of putative Type III systems. Our findings demonstrate a rich diversity within Type III RM systems.